EARNED VALUE ANALYSIS METHOD AS A COST AND TIME PERFORMANCE ANALYSIS (Case Study LAU SIMEME DAM Construction Project KSO Between PT. Wijaya Karya Persero.Tbk and PT. Bumi Karsa) - Denny Irawan; Isfenti Sadalia; Iskandar Muda (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Project construction is a series of activities that must be completed in accordance with a project contract and also at a pre-agreed cost. The important point for project completion is the accuracy in accordance with the estimate, the use of costs according to the budget while maintaining quality. However, project implementation often encountered obstacles so that the completion time stalled. The impact of late completion of this project is not only in terms of time, but has an impact on the use of costs which ultimately erodes the profit margin of a project. This is what is being faced in the Lau Simeme Dam Development Project which is an Operational Cooperation (KSO) between PT Wijaya Karya (Persero) and PT Bumi Karsa. This project costs Rp. 733 billion which began on December 22, 2017 and is estimated to be completed on April 7, 2022. The research data was taken as of December 2020, where according to the plan the project should have been completed 52.90%, but in fact it was only 13.92% completed. Based on this phenomenon, researchers conducted a research in order to solve the problem of delays and budget waste using the Earned Value Analysis approach. The results showed that there was a delay in project construction resulting in a setback in project completion with an estimated addition ( Estimated Completion Date) of 1,294 days. Due to the delay in project completion, there was an additional cost of 1.760 billion or in other words, the project cost was Rp. 665 billion while the RAB is only 663 billion. This cut the previously planned margin of 70.051 billion to 68.290 billion. In order to overcome delays in project completion, it can be done by holding work shifts,